Analisis Naskah Drama "La Tagdhob" Karya Azis W. Adhirawa dengan Menggunakan Pendekatan Struktural - Alvi Maryamul Khoiriyah; Aninda Nurfazriyautul Huda; Meri Az-Zahra (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Literary works are expressions of human thoughts and feelings expressed in writing with the power of language. Drama, as a literary genre, depicts life through staged dialogue. This research aims to analyze the drama script "La Tagdhob" by Azis W. Adhirawa using a structural approach to understand its intrinsic elements. The structuralism approach, pioneered by R. Jacobson and Ferdinand de Saussure, examines the relationships between elements in literary works to understand their meaning as a whole. Although effective in in-depth analysis, this approach ignores external context such as the author's social and cultural background. This research uses descriptive research to show that the structuralism approach is effective in identifying elements such as theme, plot, characters, setting and message, as well as emphasizing the importance of the unity of intrinsic elements. Previous research supports this approach as a systematic method in the analysis of literary works.